Developing a culture of publication: a joint enterprise writing retreat. (14th September 2015) - Garside, Joanne; Bailey, Rowan; Tyas, Moira; Ormrod, Graham; Stone, Graham; Topping, Annie; Gillibrand, Warren Peter
Abstract : Purpose: – Many students irrespective of level of study produce excellent course work which, if given support and encouragement, could clearly be of a publishable standard. Academic staff are expected to produce quality publications meeting peer-review standards although they may be relatively novice authors. All are engaged in some aspects of academic writing practices but not as frequently involved in co-production of publications emanating from student work. This activity is still at the margins of much of the student experience. The paper aims to discuss these issues. Design/methodology/approach: – Mindful of these issues, the authors designed and offered a writing programme including a writing retreat. This brought together undergraduate and postgraduate students from a range of applied disciplines (health and art, design and architecture) and their supervisors with the aim of co-producing publications and participating in a community of scholarly practice. The project was delivered over nine months. It involved four days "compulsory" attendance and included a preparatory workshop, a two day off-campus writing retreat and a dissemination event. Student and supervisors applied to participate as a team. Kirkpatrick's (2006) four-stage classic model: reaction, learning, changes in behaviour and real world results was used as a framework for the educational evaluation. Findings: – Key findings organised thematically were: supervisor-supervisee relationships; space and time; building confidence enabling successful writing and publication. Originality/value: – This paper will provide an overview of the design, content and approaches used for successful delivery of this innovative project. It will draw on examples that illustrate the different types of joint enterprise that emerged, illuminate experiences of co-production and co-authorship along with recommendations for future ventures.